The Phenomenon of Polysemy and Different Aspects of Conversion - Davidov, Yunus Jummayevich (European Journal of Life Safety and Stability (2660-9630), 2021)
This article explains the dissimilarity between polysemy and conversion by giving examples. In this study we can see that controversial aspects of the essence of polysemous words, such as metaphors, synecdoche, etc., and types of semantic transitions are discussed in detail. The concluding part of the article argues that polysemy is a multi-meaning of words within one category, and that the transfer of words to another category does not lead to the phenomenon of polysemy.